2004
DOI: 10.1149/1.1747891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti Interlayer on Ni/Si Reaction Systems

Abstract: The effects of Ti interlayer on the formation of Ni silicides on Si͑100͒ substrate was investigated. The phase and microstructure of Ni silicides during isochronal annealing treatment are monitored in situ by curvature measurement and characterized ex situ by other measurements. The addition of a thin Ti layer which formed an amorphous layer with the Si substrate acted as a diffusion barrier for the Ni atom in the early phase transformation process. The transformation temperature for the NiSi is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…This layer may contain Ti, Ni, Si, Ge and O elements (noted as Ti-related layer). Similar results have been already reported in the Ni/Ti/Si systems [15]. Considering the Ge two peaks distribution in Fig.…”
Section: Resultssupporting
confidence: 90%
“…This layer may contain Ti, Ni, Si, Ge and O elements (noted as Ti-related layer). Similar results have been already reported in the Ni/Ti/Si systems [15]. Considering the Ge two peaks distribution in Fig.…”
Section: Resultssupporting
confidence: 90%
“…After selective etching (to remove the unreacted metal), bubble formation was not observed as in the 350°C sample, indicating full consumption of metal layers. This temperature range is similar to that of Chiu et al [10] observed for c-Si, and larger than layer inversion starting at 550°C, observed by Nygren et al [7] for pure Ni on poly-Si. At temperatures above 700°C, an increase in the sheet resistance is observed mainly due to the start of silicide/poly-Si layer inversion and agglomeration.…”
Section: Resultssupporting
confidence: 90%
“…High R s values above 10 X/sq. was again observed for the sample obtained at the silicidation temperature of 350°C, probably due to the uncompleted formation of the Ni(Pt)Si alloy [9,10]. Post-annealing treatments confirm this assumption as the sheet resistance diminishes to half of the initial value (Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Based on the results of XRD in Fig. 5, the majority of Ti atoms appear near the surface of the film and it can be assumed that Ti does not combine with Ni or Si to form a compound [10]. Moreover, there was a thin surface Ti-related layer (maybe Ti w Ni x Si y O z or a mixture of compounds containing these elements) above the NiSi layer.…”
Section: Resultsmentioning
confidence: 99%